1996
DOI: 10.1172/jci118889
|View full text |Cite
|
Sign up to set email alerts
|

The receptor for advanced glycation end products (RAGE) is a central mediator of the interaction of AGE-beta2microglobulin with human mononuclear phagocytes via an oxidant-sensitive pathway. Implications for the pathogenesis of dialysis-related amyloidosis.

Abstract: An important component of amyloid fibrils in dialysisrelated amyloidosis is a form of ␤ 2 microglobulin modified with advanced glycation end products (AGEs) of the Maillard reaction, known as AGE-␤ 2 M. We demonstrate here that the interaction of AGE-␤ 2 M with mononuclear phagocytes (MPs), cells important in the pathogenesis of the inflammatory arthropathy of dialysis-related amyloidosis, is mediated by the receptor for AGEs, or RAGE.125 I-AGE-␤ 2 M bound to immobilized RAGE or to MPs in a specific, dose-depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
171
2
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 278 publications
(177 citation statements)
references
References 36 publications
3
171
2
1
Order By: Relevance
“…In this context, previous studies indicated that heterogenous AGEs, especially those derived from in vivo sources, were signal-transducing ligands of RAGE. Specifically, interaction of AGE-␤ 2 -microglobulin, isolated from the urine of subjects with renal failure and DRA, with cellular RAGE resulted in enhanced MP migration and generation of proinflammatory cytokines such as tumor necrosis factor-␣ (16). Since recent studies have shown AGE-␤ 2 M itself to be quite heterogeneous, composed at least in part of AGEs such as pentosidine, CML, and imidizalone (55)(56)(57), it was important to begin to delineate those specific AGEs that interacted with RAGE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, previous studies indicated that heterogenous AGEs, especially those derived from in vivo sources, were signal-transducing ligands of RAGE. Specifically, interaction of AGE-␤ 2 -microglobulin, isolated from the urine of subjects with renal failure and DRA, with cellular RAGE resulted in enhanced MP migration and generation of proinflammatory cytokines such as tumor necrosis factor-␣ (16). Since recent studies have shown AGE-␤ 2 M itself to be quite heterogeneous, composed at least in part of AGEs such as pentosidine, CML, and imidizalone (55)(56)(57), it was important to begin to delineate those specific AGEs that interacted with RAGE.…”
Section: Discussionmentioning
confidence: 99%
“…Mononuclear Phagocytes-Previous studies from our laboratory indicated that MP properties are significantly modulated upon ligation of RAGE by heterogeneous AGEs, either those prepared in vitro or those derived from in vivo sources, such as AGEs isolated from diabetic plasma, or AGE-␤ 2 -microglobulin isolated and purified from the urine/plasma of subjects with DRA (16). It was thus important to determine if CML adducts, present in these preparations, could activate RAGE on MPs causing cellular migration and activation in this setting (54).…”
Section: Cml-modified Adducts Mediate Cellular Activation In Vitro Amentioning
confidence: 99%
“…A second, non-mutually exclusive, possibility is that overproduction of Hu␤ 2 m has biologic effects that converge with those of the UPR. A significant body of literature shows that serum ␤ 2 m becomes glycated over time, and that advanced glycation end products interact with receptors for advanced glycation end products, leading to NF-kB activation, which can amplify immune and inflammatory responses (27,28). For example, ␤2-microglobulin modified with advanced glycation end products delays monocyte apoptosis and results in increased production of proinflammatory TNF␣ and IL-1␤ (29).…”
Section: Discussionmentioning
confidence: 99%
“…of iodination damage in enhancing the interaction of proteins with RAGE is the fact that several proteins when iodinated, do not bind this receptor, as is the case of native albumin and native ␤ 2 -microglobulin, whereas their iodinated advanced glycation end products do (Miyata et al, 1996;Schmidt et al, 1994).…”
Section: Sousa Et Almentioning
confidence: 99%